1989
DOI: 10.1090/s0002-9939-1989-0942634-7
|View full text |Cite
|
Sign up to set email alerts
|

The Cauchy functional equations in distributions

Abstract: Abstract.The Pompeiu functional equation is defined by Neagu for Schwartz distributions. His method is extended to the four Cauchy functional equations by means of two new operators Q* and R* on 3'(I).The Cauchy equations in distributions reduce to the classical equations when the solutions are regular distributions, i.e. locally integrable functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…In order to represent the left-hand side of equation (1.2), one needs to define two additional operators.This will be discussed in the next section. Moreover, we remark that the operator (2+ is similar to the operator Q defined and studied in [8,12]. The adjoints of these operators are Q* and Q*_ and are defined from 2'{I) into 2'il2) by…”
Section: ) Dxp[s; T] = P[ds; T] and D2p[s; T] = P[s; Dt]mentioning
confidence: 97%
See 2 more Smart Citations
“…In order to represent the left-hand side of equation (1.2), one needs to define two additional operators.This will be discussed in the next section. Moreover, we remark that the operator (2+ is similar to the operator Q defined and studied in [8,12]. The adjoints of these operators are Q* and Q*_ and are defined from 2'{I) into 2'il2) by…”
Section: ) Dxp[s; T] = P[ds; T] and D2p[s; T] = P[s; Dt]mentioning
confidence: 97%
“…The proof of these properties is analogous to [12] and thus we shall omit it. In order to define equation ( 1.2) in distributions one needs to define a tensor product operator on 2'{I) x 3'{I)…”
Section: Some Operators On 2'mentioning
confidence: 99%
See 1 more Smart Citation
“…Many well-known functional equations have been studied in the Schwartz distributions (see [2], [3], [4], [5], [10] and [11] etc.). Actually it was shown that most of these functional equations in the distributions reduce to the classical ones.…”
Section: Introductionmentioning
confidence: 99%
“…This functional equation is known as the Pompeiu .furtc.tiortal equation [3,4]. To see this, add 1 to both sides of (PE) and write F(x) 1 + f(x).…”
Section: Introductionmentioning
confidence: 99%